A high-strength flame-retardant composite material for pipelines and preparation method thereof

By adding fiber reinforced filler and flame retardant to the PA12T pipe, a high-strength flame retardant composite material was prepared, which solved the problem of insufficient mechanical and fire resistance performance in long carbon chain semi-aromatic nylon in pipe applications, and achieved higher mechanical and flame retardant performance.

CN119432066BActive Publication Date: 2025-03-14SHANDONG JINSHUNDA PIPE IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510027992.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-14
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

When used as a pipe, long carbon chain semi-aromatic nylon has insufficient mechanical properties and fire resistance, making it difficult to promote and use.

Method used

PA12T is used as the matrix resin, combined with fiber reinforced filler, melamine polyphosphate, concave and concave rock stone and graphene, and high-strength flame retardant composite materials are prepared through the process of high-mixer and twin-screw extruder.

Benefits of technology

It significantly improves the mechanical properties and flame retardant properties of pipeline composite materials, overcomes the problems of water absorption and mechanical properties of PA12T in high temperature and humidity environments, and is suitable for areas with high heat resistance and dimensional stability requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure RBZUBZOFKICOSPI4V5NZEZRPLCIHGXIPCRQ8NDE4
    Figure RBZUBZOFKICOSPI4V5NZEZRPLCIHGXIPCRQ8NDE4
  • Figure WT6MGV5CY82ULTFL18PQIYL8X60N1VISX0IBQYZH
    Figure WT6MGV5CY82ULTFL18PQIYL8X60N1VISX0IBQYZH
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer composite materials, and specifically relates to a high-strength flame-retardant composite material for pipelines and a preparation method thereof. The high-strength flame-retardant composite material for pipelines comprises the following components in parts by weight: 70-80 parts of PA12T, 10-15 parts of toughening agent, 20-30 parts of fiber-reinforced filler, 8-16 parts of melamine polyphosphate, 1-6 parts of attapulgite, 2-4 parts of graphene, 0-3 parts of coupling agent, 0-3 parts of lubricant, and 0-3 parts of antioxidant. MPP is a N and P dual-element synergistic flame retardant with better flame retardant effect. Through the adsorption of attapulgite, the dispersibility of MPP in PA12T can be improved to prevent precipitation. As a common flame-retardant carbonizing agent, graphene has a lamellar structure that can not only play a role in resisting molten droplets; and it interacts with the attapulgite of the rod-like structure, which promotes the dispersibility of graphene, attapulgite and melamine polyphosphate in nylon resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials, and particularly relates to a high-strength flame-retardant composite material for pipelines and a preparation method thereof. Background Art

[0002] Fiber reinforced composites are a type of composite material composed of resin and fiber. In fiber reinforced composites, the fibers act as reinforcing materials, and their winding direction affects the performance of the material, while the matrix material protects the fibers and transfers the load. By rationally selecting fiber types, controlling manufacturing processes and processing methods, fiber reinforced composites with different properties can be obtained. Fiber reinforced composites have the advantages of high strength, low density, and corrosion resistance, and are an important alternative to steel pipes. At present, they have been widely used in gathering and transportation pipelines, water injection pipelines, and other fields.

[0003] Traditional metal materials have major drawbacks in the process of pipe development and are prone to failure, while fiber-reinforced composite materials have higher technical and economic advantages. Applying fiber-reinforced composite materials to pipeline transmission can not only improve efficiency and production capacity, but also reduce environmental impact and reduce operating costs.

[0004] Polyamide, also known as nylon, is a general term for polymers containing amide groups in the repeating units of the main chain of macromolecules. Currently, the nylon produced and used in large quantities is mainly aliphatic nylon. Generally speaking, aliphatic nylon has the advantages of fast crystallization speed, high crystallinity, good flexibility and high mechanical strength, which makes crystalline polyamide represented by nylon 6, nylon 66, nylon 1010 and nylon 1212 widely used as fibers and general engineering plastics. However, the operating temperature of these nylons generally does not exceed 80°C. At the same time, when the ambient humidity is high, water absorption will cause a large change in the volume of the material and a decrease in mechanical properties, which limits their application in fields with high requirements for heat resistance and dimensional stability. Therefore, there is a continuous demand for the development of polyamides with good heat resistance, good dimensional stability and mechanical properties. In order to meet the requirements for heat resistance of materials, DuPont and others began to study the introduction of aromatic rings into the main chain of macromolecules around 1960, and commercialized polyisophthalamide, a wholly aromatic polyamide, in 1967 for use as fibers and face cloths, mainly to produce fire-resistant and heat-resistant protective clothing. However, wholly aromatic polyamides have high melting points and are difficult to process, making them difficult to prepare into tubular devices. PA12T, as a long carbon chain semi-aromatic nylon, can be used as electrical / electronic components, automotive components, and especially as a substrate molding material for electronic components due to its high crystallinity, low water absorption, and excellent heat resistance, and has broad application prospects. However, when PA12T is used as a pipe, it still faces deficiencies in mechanical properties and fire resistance, making it difficult to promote its use. Summary of the invention

[0005] The purpose of the present invention is to prepare a high-strength flame-retardant composite material for pipelines, which overcomes the technical problems of poor mechanical strength and low flame retardancy of long carbon chain semi-aromatic nylon and is suitable for use as a pipeline material.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0008] PA12T 70-80 parts, toughening agent 10-15 parts, fiber reinforced filler 20-30 parts, melamine polyphosphate 8-16 parts, attapulgite 1-6 parts, graphene 2-4 parts, coupling agent 0-3 parts, lubricant 0-3 parts, antioxidant 0-3 parts.

[0009] PA12T is made of long carbon chain dodecane diamine and aromatic dibasic acid terephthalic acid through high temperature and high compression polymerization. Its melting point is about 301℃ and its glass transition temperature is about 125℃. It has higher melt processability than PA6T and better dimensional stability than PA9T. From the perspective of molecular structure, the longer the carbon chain, the lower the concentration of amide bonds. Due to the extremely low amide bond content, its water absorption rate is lower than that of high temperature resistant nylons such as PA6T, PA46, PA9T and PA10T. It has good dimensional stability, good fluidity and excellent processing performance. In addition, due to the ultra-long alkyl group of dodecane diamine, its impact performance is also good. Using PA12T as the base resin of pipeline composite materials can improve the mechanical properties of composite materials to a certain extent.

[0010] In order to improve the flame retardant properties of PA12T, the present invention adds a certain amount of melamine polyphosphate (MPP) flame retardant. Both MPP and MCA are derivatives of melamine and are a type of environmentally friendly flame retardant. However, MPP is a N and P dual-element synergistic flame retardant with better flame retardant effect. In addition, MPP also has the advantages of good thermal stability, high decomposition temperature, low smoke, low water solubility, and no water absorption. When the MPP flame retardant decomposes, it can generate a large amount of non-combustible gases such as water vapor, N2, CO2 and NH3. These gases not only dilute the combustibles and oxygen concentration, but also cover the surface of the material, separating the combustion area of ​​the material from the air. In addition, when the MPP flame retardant is heated at high temperature, it will decompose into small molecular condensation products, which can delay or prevent the decomposition of the polymer and increase the probability of carbonization. The carbon layer generated at high temperature is very stable, can isolate oxygen and heat, and is a dense protective layer. However, when the material burns, the MPP flame retardant will cause droplet heat transfer. That is, when the flame retardant material is heated and burned, the material will melt and flow, resulting in molten droplets, which can easily cause the spread of fire. In addition, due to the poor compatibility of MPP with the matrix resin, the MPP flame retardant is prone to precipitation during the processing and storage period, affecting the appearance of the product.

[0011] In order to further improve the flame retardant effect of the MPP flame retardant and improve its precipitation properties, the present invention adds a certain amount of attapulgite and graphene. The large surface area and surface physical and chemical structure of attapulgite create its excellent adsorption. Through the adsorption of attapulgite, the dispersion performance of MPP in PA12T can be improved to prevent its precipitation. In addition, attapulgite contains a rich internal pore structure, and the pore contains a certain amount of adsorbed water. In the early stage of combustion, the adsorbed water will escape from the pore to absorb the heat emitted during combustion, reduce the heat release during material combustion, and prevent the combustion from proceeding. When the material continues to burn, the attapulgite structure is destroyed, and the crystal water lost in the structure can effectively absorb the heat released by the material and produce gas that isolates combustion, playing a flame retardant role. As a common flame retardant carbonizing agent, graphene has a lamellar structure that can not only play a role in resisting molten droplets; but also interacts with the rod-shaped attapulgite, which promotes the dispersion of graphene, attapulgite and melamine polyphosphate in nylon resin.

[0012] Furthermore, the toughening agent is at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene propylene diene monomer rubber.

[0013] Furthermore, the fiber-reinforced filler is at least one of glass fiber and carbon fiber.

[0014] Furthermore, the fiber-reinforced filler is alkali-free chopped glass fiber. Alkali-free chopped glass fiber has high tensile strength and elastic coefficient, can absorb a large amount of impact energy within the elastic limit, and is suitable for use in pipeline fields that require high strength and rigidity.

[0015] Furthermore, the size of the attapulgite is 0.5-4 μm.

[0016] Furthermore, the coupling agent is at least one of a borate coupling agent, an aluminate coupling agent, a silane coupling agent, and a titanate coupling agent.

[0017] Furthermore, the lubricant is at least one of silicone powder, polytetrafluoroethylene, amide wax, talcum powder, calcium stearate, and zinc stearate.

[0018] Furthermore, the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant.

[0019] On the other hand, the present invention also provides a method for preparing a high-strength flame-retardant composite material for a pipeline, comprising the following steps:

[0020] (1) PA12T, toughening agent, melamine polyphosphate, attapulgite, graphene, coupling agent, lubricant, and antioxidant are respectively placed in a high-speed mixer and mixed evenly to obtain a mixture;

[0021] (2) The mixed material is added into a twin-screw extruder through a main feed port, and the fiber-reinforced filler is added into the twin-screw extruder through a side feed port. The mixed material is melt-extruded, dried, and pelletized by the twin-screw extruder to obtain a high-strength flame-retardant composite material for pipes.

[0022] Furthermore, the screw speed of the twin-screw extruder is 400-600 r / min, and the extrusion temperature is 300-330°C.

[0023] Beneficial effects: The present invention uses PA12T as a matrix resin, fiber as a reinforcing filler, melamine polyphosphate, attapulgite, and graphene as composite flame retardant and reinforcing fillers to prepare a high-strength flame retardant composite material for pipelines. Using PA12T as the base resin of the pipeline composite material can improve the mechanical properties of the composite material to a certain extent. MPP is a N and P dual-element synergistic flame retardant with better flame retardant effect. In addition, MPP also has the advantages of good thermal stability, high decomposition temperature, low smoke, low water solubility, and no water absorption. In order to further improve the flame retardant effect of the MPP flame retardant and improve its precipitation properties, the present invention adds a certain amount of attapulgite and graphene. Through the adsorption of attapulgite, the dispersion performance of MPP in PA12T can be improved to prevent its precipitation. As a common flame retardant carbonizing agent, graphene has a lamellar structure that can not only play a role in resisting molten droplets; but also interacts with the rod-shaped attapulgite to promote the dispersion performance of graphene, attapulgite and melamine polyphosphate in nylon resin. DETAILED DESCRIPTION

[0024] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0025] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0027] Example 1

[0028] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0029] 70 parts of PA12T, 10 parts of toughening agent, 20 parts of fiber reinforced filler, 10 parts of melamine polyphosphate, 2 parts of attapulgite, 2 parts of graphene, 1 part of coupling agent, 1 part of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is silicone powder; and the antioxidant is antioxidant 1098.

[0030] Example 2

[0031] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0032] 80 parts of PA12T, 15 parts of toughening agent, 30 parts of fiber reinforced filler, 13 parts of melamine polyphosphate, 4 parts of attapulgite, 4 parts of graphene, 3 parts of coupling agent, 3 parts of lubricant, and 3 parts of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is polytetrafluoroethylene; and the antioxidant is antioxidant 1098.

[0033] Example 3

[0034] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0035] 70 parts of PA12T, 15 parts of toughening agent, 20 parts of fiber reinforced filler, 13 parts of melamine polyphosphate, 2 parts of attapulgite, 4 parts of graphene, 1 part of coupling agent, 3 parts of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0036] Example 4

[0037] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0038] 73 parts of PA12T, 11 parts of toughening agent, 22 parts of fiber reinforced filler, 11 parts of melamine polyphosphate, 2.5 parts of attapulgite, 2.5 parts of graphene, 1.5 parts of coupling agent, 2 parts of lubricant, and 1.5 parts of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0039] Example 5

[0040] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0041] 77 parts of PA12T, 14 parts of toughening agent, 27 parts of fiber reinforced filler, 12 parts of melamine polyphosphate, 3.5 parts of attapulgite, 3.5 parts of graphene, 2.5 parts of coupling agent, 2.5 parts of lubricant, and 2 parts of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is polytetrafluoroethylene; and the antioxidant is antioxidant 1098.

[0042] Example 6

[0043] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0044] 75 parts of PA12T, 12 parts of toughening agent, 25 parts of fiber reinforced filler, 8 parts of melamine polyphosphate, 3 parts of attapulgite, 3 parts of graphene, 2 parts of coupling agent, 1 part of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0045] Example 7

[0046] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0047] 75 parts of PA12T, 12 parts of toughening agent, 25 parts of fiber reinforced filler, 16 parts of melamine polyphosphate, 3 parts of attapulgite, 3 parts of graphene, 2 parts of coupling agent, 1 part of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0048] Example 8

[0049] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0050] 75 parts of PA12T, 12 parts of toughening agent, 25 parts of fiber reinforced filler, 12 parts of melamine polyphosphate, 1 part of attapulgite, 3 parts of graphene, 2 parts of coupling agent, 1 part of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0051] Example 9

[0052] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0053] 75 parts of PA12T, 12 parts of toughening agent, 25 parts of fiber reinforced filler, 12 parts of melamine polyphosphate, 6 parts of attapulgite, 3 parts of graphene, 2 parts of coupling agent, 1 part of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0054] Example 10

[0055] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0056] 75 parts of PA12T, 12 parts of toughening agent, 25 parts of fiber reinforced filler, 12 parts of melamine polyphosphate, 3 parts of attapulgite, 3 parts of graphene, 2 parts of coupling agent, 1 part of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0057] Comparative Example 1

[0058] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0059] 75 parts of PA12T, 12 parts of toughening agent, 25 parts of fiber reinforced filler, 12 parts of melamine polyphosphate, 0 parts of attapulgite, 6 parts of graphene, 2 parts of coupling agent, 1 part of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0060] Comparative Example 2

[0061] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0062] 75 parts of PA12T, 12 parts of toughening agent, 25 parts of fiber reinforced filler, 12 parts of melamine polyphosphate, 6 parts of attapulgite, 0 parts of graphene, 2 parts of coupling agent, 1 part of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0063] Comparative Example 3

[0064] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0065] 75 parts of PA12T, 12 parts of toughening agent, 25 parts of fiber reinforced filler, 12 parts of melamine polyphosphate, 3 parts of attapulgite, 1 part of graphene, 2 parts of coupling agent, 1 part of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0066] Comparative Example 4

[0067] A high-strength flame-retardant composite material for pipes, comprising the following components in parts by weight:

[0068] 75 parts of PA12T, 12 parts of toughening agent, 25 parts of fiber reinforced filler, 12 parts of melamine polyphosphate, 3 parts of attapulgite, 6 parts of graphene, 2 parts of coupling agent, 1 part of lubricant, and 1 part of antioxidant; the toughening agent is maleic anhydride grafted ethylene-octene copolymer; the fiber reinforced filler is alkali-free chopped glass fiber; the size of the attapulgite is 1 μm; the coupling agent is KH550; the lubricant is talc; and the antioxidant is antioxidant 1098.

[0069] The preparation method of the high-strength flame-retardant composite material for pipelines of the above-mentioned Examples 1-10 and Comparative Examples 1-4 comprises the following steps:

[0070] (1) PA12T, toughening agent, melamine polyphosphate, attapulgite, graphene, coupling agent, lubricant, and antioxidant are respectively placed in a high-speed mixer and mixed evenly to obtain a mixture;

[0071] (2) The mixed material is added into a twin-screw extruder through a main feed port, and the fiber-reinforced filler is added into the twin-screw extruder through a side feed port. The mixed material is melt-extruded, dried, and pelletized by the twin-screw extruder to obtain a high-strength flame-retardant composite material for pipes. The screw speed of the twin-screw extruder is 500 r / min, and the extrusion temperature is 315°C.

[0072] Performance test: The tensile strength (ISO 527-2), notched impact strength (ISO 179), and flame retardancy (UL94) of the high-strength flame-retardant composite material samples for pipes prepared in Examples 1-10 and Comparative Examples 1-4 were tested respectively. The molten droplets and surface precipitation of the samples were observed. The surface precipitation was divided into four grades: A, B, C, and D, and the precipitation from A to D indicated that the precipitation was getting more and more serious.

[0073]

[0074]

[0075] As can be seen from Table 1, the present invention uses PA12T as a matrix resin, fiber as a reinforcing filler, melamine polyphosphate, attapulgite, and graphene as composite flame retardant and reinforcing fillers to prepare a high-strength flame retardant composite material for pipelines. Using PA12T as the base resin of the pipeline composite material can improve the mechanical properties of the composite material to a certain extent. MPP is a N and P dual-element synergistic flame retardant, and has a better flame retardant effect. In addition, MPP also has the advantages of good thermal stability, high decomposition temperature, low smoke, low water solubility, and no water absorption. It can be seen from Example 10 and Comparative Examples 1-2 that the dispersibility of MPP in PA12T can be improved by the adsorption of attapulgite, and its precipitation phenomenon can be prevented. As a common flame retardant carbonizing agent, graphene has a lamellar structure that can not only play a role in resisting molten droplets; but also interacts with the rod-like structure of attapulgite, which promotes the dispersibility of graphene, attapulgite and melamine polyphosphate in nylon resin. When the comparative examples 1 and 2 lack one-dimensional rod-shaped attapulgite or two-dimensional layered graphene, it is easy to cause uneven dispersion of graphene, attapulgite and melamine polyphosphate, which not only affects the mechanical properties of the product, but also leads to a decrease in the flame retardant properties of the composite material. Comparative Examples 3-4 show that when graphene is used as a nano-layered filler, it is difficult to construct an anti-drip network when its dosage is too small, and the flame retardant enhancement effect is insufficient; when its dosage is too large, agglomeration problems are likely to occur, affecting the improvement of product performance.

[0076] In summary, the specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments under the concept of the present invention, but are not intended to limit the present invention; those skilled in the art can make adaptive adjustments within the concept and protection scope of the present invention.

[0077] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A high-strength flame-retardant composite material for pipelines, characterized in that: Contains the following components in parts by weight: PA12T 70-80 parts, toughening agent 10-15 parts, fiber reinforced filler 20-30 parts, melamine polyphosphate 8-16 parts, attapulgite 1-6 parts, graphene 2-4 parts, coupling agent 0-3 parts, lubricant 0-3 parts, antioxidant 0-3 parts; The fiber-reinforced filler is alkali-free chopped glass fiber; The size of the attapulgite is 0.5-4 μm.

2. The high-strength flame-retardant composite material for pipes according to claim 1, characterized in that: The toughening agent is at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene propylene diene monomer rubber.

3. The high-strength flame-retardant composite material for pipes according to claim 1, characterized in that: The coupling agent is at least one of a borate coupling agent, an aluminate coupling agent, a silane coupling agent, and a titanate coupling agent.

4. The high-strength flame-retardant composite material for pipes according to claim 1, characterized in that: The lubricant is at least one of silicone powder, polytetrafluoroethylene, amide wax, talcum powder, calcium stearate, and zinc stearate.

5. The high-strength flame-retardant composite material for pipes according to claim 1, characterized in that: The antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant.

6. A method for preparing a high-strength flame-retardant composite material for pipelines according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) PA12T, toughening agent, melamine polyphosphate, attapulgite, graphene, coupling agent, lubricant, and antioxidant are respectively placed in a high-speed mixer and mixed evenly to obtain a mixture; (2) The mixed material is added into a twin-screw extruder through a main feed port, and the fiber-reinforced filler is added into the twin-screw extruder through a side feed port. The mixed material is melt-extruded, dried, and pelletized by the twin-screw extruder to obtain a high-strength flame-retardant composite material for pipes.

7. The method for preparing a high-strength flame-retardant composite material for pipelines according to claim 6, characterized in that: The screw speed of the twin-screw extruder is 400-600r / min, and the extrusion temperature is 300-330℃.

Citation Information

Patent Citations

  • High-glow-wire initiation temperature flame-retardant nylon composition

    CN103304992A

  • High thermal conductivity flame-retardant nylon composite material and preparation method thereof

    CN105295360A